Research on selecting the F propellant composition and developing the propulsion equation for the launching bomb using Matlab software - Nguyễn Văn Hùng; Trần Hữu Thành; Hoàng Văn Hùng; Lê Viết Hà (Journal of Military Science and Technology, 2024)
The paper presents the basis for selecting the F propellant composition for the launching bomb and developing the propulsion algorithm using Matlab software. Theoretical and experimental research results highlight the impact of certain components on energy characteristics and ballistic performance, leading to the establishment of requirements for the F propellant. This forms a critical foundation for setting technical conditions to develop a new F propellant grade with properties equivalent to those of foreign products.